Comparative Analysis Of The Human Soul In Yoruba Philosophy And Transcendental Philosophy (Journal of Namibian Studies : History Politics Culture, 2024)
This research paper conducts a comparative analysis of the human soul in Yoruba philosophy and Transcendental Philosophy (Hikmat al-muta’aliyah), exploring their similarities and differences. Yoruba philosophy emphasizes the interconnectedness of humans and the spiritual realm and the immortality of the soul. In contrast, Hikmat al-muta’aliyah, as discussed by scholars like Mullā Ṣadrā and Allameh Tabatabi, focuses on the soul’s metaphysical aspects and divine connection. Through library-based research using a descriptive, analytical, and critical approach, the study compares key texts and ideas from both traditions to uncover their philosophical principles regarding the soul. Key distinctions arise in their discussions of the non-material world and the soul's origin, while both traditions agree on viewing the soul as an immaterial, independent entity and a philosophical foundation. Ultimately, this comparative study aims to enrich our understanding of the human soul from various cultural and philosophical perspectives, highlighting universal aspects of existence as well as unique nuances in each tradition's interpretation.